A tumor profile in Patau syndrome (trisomy 13). Issue 8 (25th May 2017) - Satgé, Daniel; Nishi, Motoi; Sirvent, Nicolas; Vekemans, Michel; Chenard, Marie‐Pierre; Barnes, Ann
Abstract : Individuals with trisomic conditions like Down syndrome and Edwards syndrome are prone to certain types of malignancy. However, for Patau syndrome (constitutional trisomy 13), which occurs in 1/10, 000–1/20, 000 live births, the tumor profile has not been well characterized. An awareness of susceptibility to malignancies can improve care of affected individuals, as well as further our understanding of the contribution of trisomy to carcinogenesis. Therefore, we conducted an extensive review of the literature; we found 17 malignancies reported in individuals with Patau syndrome. These comprised eight embryonic tumors, three leukemias, two malignant germ cell tumors, two carcinomas, a malignant brain tumor, and a sarcoma. Benign tumors were mainly extragonadal teratomas. The small number of reported malignant tumors suggests that there is not an increased risk of cancer in the context of trisomy 13. The tumor profile in Patau syndrome differs from that observed in Edwards syndrome (trisomy 18) and Down syndrome (trisomy 21), suggesting that the supernumerary chromosome 13 could promote particular tumor formations as it does particular malformations. No general and direct relationships of tumor occurrence with organ weight, congenital malformations, histological changes, or presence of tumor suppressor genes on chromosome 13 were observed. However, some tumors were found in tissues whose growth and development are controlled by genes mapping to chromosome 13. Recent reports of successful outcomes following surgical treatment and adapted chemotherapy indicate that treatment of cancer is possible in Patau syndrome.